2005
DOI: 10.1161/01.hyp.0000184226.99196.b5
|View full text |Cite
|
Sign up to set email alerts
|

Human Urotensin II Accelerates Foam Cell Formation in Human Monocyte-Derived Macrophages

Abstract: Abstract-Human urotensin II (U-II), the most potent vasoconstrictor peptide identified to date, and its receptor (UT) are involved in hypertension and atherosclerosis. Acyl-coenzyme A:cholesterol acyltransferase-1 (ACAT-1) converts intracellular free cholesterol into cholesterol ester (CE) for storage in lipid droplets and plays an important role in the formation of macrophage-derived foam cells in atherosclerotic lesions. We examined the effects of U-II on ACAT-1 expression and CE accumulation in human monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 49 publications
4
91
0
2
Order By: Relevance
“…UII and its receptor have both been linked to macrophage function, particularly the formation of foam cells [12]. This is consistent with our findings of increased CCL2 expression and monocyte adhesion in vitro, and the attenuation of these effects with UT antagonism in a high-glucose environment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…UII and its receptor have both been linked to macrophage function, particularly the formation of foam cells [12]. This is consistent with our findings of increased CCL2 expression and monocyte adhesion in vitro, and the attenuation of these effects with UT antagonism in a high-glucose environment.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, chronic UII infusion has been shown to enhance macrophage foam cell formation [12] and atherosclerosis in high-fat-fed Apoe knockout (KO) mice [13]. While UT antagonism has been investigated in diabetic nephropathy [14,15], little is known of the role of UII in the development of diabetes-associated atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Other laboratories have shown that the cytokine transforming growth factor-b1 (TGF-b1) also increases ACAT1 activity in human monocytes (43). In addition, urotensin II, the potent vasoconstrictor peptide that leads to hypertension and atherosclerosis in humans, was shown to upregulate the ACAT1 gene expression in human macrophages (44). In contrast, the human ACAT1 gene expression was downregulated by adiponectin, an adipocytokine that exerts many antiatherosclerotic effects in cell culture studies (45).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of U and UT expression are up-regulated by inflammatory cytokines, such as interferon-, IL-6, and IL-1 , and by hypoxia (ischemia) and mechanical stimuli [34][35][36][37] . U contributes to the development of atherosclerosis by inducing macrophage foam cell formation, EC and VSMC proliferation, and extracellular matrix production 14,38,39) . U accelerates macrophage foam cell formation by up-regulating acyl-CoA:cholesterol acyltransferase-1 38) , and has synergistic interactions with mildly oxidized LDL in inducing VSMC proliferation at the highest rate among vasoactive agents 40) .…”
Section: Vsmc Mø Mømentioning
confidence: 99%
“…U contributes to the development of atherosclerosis by inducing macrophage foam cell formation, EC and VSMC proliferation, and extracellular matrix production 14,38,39) . U accelerates macrophage foam cell formation by up-regulating acyl-CoA:cholesterol acyltransferase-1 38) , and has synergistic interactions with mildly oxidized LDL in inducing VSMC proliferation at the highest rate among vasoactive agents 40) . Our recent study showed that chronic infusion of U into apoE-knockout mice enhances atherosclerotic lesions 41) .…”
Section: Vsmc Mø Mømentioning
confidence: 99%